Simulation of Solar Cell Device Performance Based on Hydrogenated Microcrystal Silicon (µc-Si:H) With Finite Element Method (FEM) - La Ode Asmin (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2022)
The structure and thickness of the solar cell device layer have a big impact on how well the solar cell works. There for, the aim of this study was to examine how hydrogenated microcrystalline silicon solar cells’ thickness and device structure affected how well they work. Simulation or modeling of the structure in one dimension (1D) is used for the analysis. MATLAB programming was used to analyze the simulation result. The optical band gap changes due to the influence of the structure, therefore the thickness of the p-, I, and n layers are kept constant at 250 Å, 9000 Å, and 250 Å respectively. The results showed that the maximum performance is obtained at the optical band gap, Eci = 1,39 eV, and the resulting power is 0.063465 Watt. Whereas in the simulation of the effect of the thickness on the i-layer, the optical band gap is set to a constant value of Eci = 1,4 eV, while the thickness of the p-layer and n-layer is set to 250 Å. The results also indicate that the maximum performance is at the i-layer thickness of 9000 Å and the power generated is 0.063364 Watt.